Antibiotic sorption onto microplastics in water: A critical review of the factors, mechanisms and implications. (15th April 2023) - Stapleton, Michael J.; Ansari, Ashley J.; Hai, Faisal I.
Highlights: Functional groups and antibiotic ionic properties govern adsorption on microplastics. Electrostatic and hydrophobic interactions are the main mechanisms for sorption. Polymer type and degree of weathering heavily influence sorption. pH and salinity of a solution found to affect sorption capacity. Standardised methodology for antibiotic sorption experiments is required. Abstract: Microplastics as vectors for contaminants in the environment is becoming a topic of public interest. Microplastics have been found to actively adsorb heavy metals, per-fluorinated alkyl substances (PFAS), polychlorinated biphenyls (PCBs), polyaromatic hydrocarbons (PAHs), pharmaceuticals and personal care products (PPCPs) and polybrominated diethers (PBDs) onto their surface. Particular interest in microplastics capacity to adsorb antibiotics needs further attention due to the potential role this interaction plays on antibiotic resistance. Antibiotic sorption experiments have been documented in the literature, but the data has not yet been critically reviewed. This review aims to comprehensively assess the factors that affect antibiotic sorption onto microplastics. It is recognised that the physico- chemical properties of the polymers, the antibiotic chemical properties, and the properties of the solution all play a crucial role in the antibiotic sorption capacity of microplastics. Weathering of microplastics was found to increase the antibiotic sorption capacity by up to 171%. An increase in solution salinity was found to decrease the sorption of antibiotics onto microplastics, in some instances by 100%. pH also has a substantial effect on sorption capacity, illustrating the significance of electrostatic interactions on the sorption of antibiotics onto microplastics. The need for a uniform experimental design when testing antibiotic sorption is highlighted to remove inconsistencies in the data currently presented. Current literature examines the link between antibiotic sorption and antibiotic resistance, however, further studies are still required to fully understand this emerging global crisis. Graphical abstract: Image, graphical abstract